2021
DOI: 10.2174/1874312902115010057
|View full text |Cite
|
Sign up to set email alerts
|

Does Disease Activity Influence the Levels of Uric Acid in Psoriatic Arthritis?

Abstract: Background: Hyperuricemia is not only associated with the development of gout but also with renal and vascular dysfunction. The prevalence of this condition has already been studied in psoriasis, but there are a few studies that have been carried out in psoriatic arthritis (PsA). Some studies have shown an association with metabolic syndrome, while others with the extent of cutaneous involvement, but there are no studies that have evaluated the disease activity with compound indexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A disorder that is associated with both Ps and metabolic syndrome is hyperuricemia, which is also an independent risk factor for CVD and Ps. The increased risk of obesity in the psoriatic population contributes to increased serum uric acid levels [51], which consequently leads to the impaired migration and proliferation of endothelial cells. The presence of uric acid in the blood initiates the inflammatory process and fat accumulation in liver cells, and contributes to oxidative stress in adipocytes.…”
Section: Hyperuricemiamentioning
confidence: 99%
“…A disorder that is associated with both Ps and metabolic syndrome is hyperuricemia, which is also an independent risk factor for CVD and Ps. The increased risk of obesity in the psoriatic population contributes to increased serum uric acid levels [51], which consequently leads to the impaired migration and proliferation of endothelial cells. The presence of uric acid in the blood initiates the inflammatory process and fat accumulation in liver cells, and contributes to oxidative stress in adipocytes.…”
Section: Hyperuricemiamentioning
confidence: 99%
“…Lai observed that a signifi cant proportion of patients with psoriatic arthritis have asymptomatic hyperuricemia, which is closely related to body mass index but not to the severity of skin lesions, joint infl ammation and renal function [5]. Chu et al found that hyperuricemia in individuals with psoriatic arthritis is associated with metabolic factors and not so much with disease activity [6].…”
Section: Introductionmentioning
confidence: 99%